FINANCIAL SUPPORT FOR INNOVATIVE DEVELOPMENT OF AGRO-INDUSTRIAL ENTERPRISES (INNOVATIVE ECONOMY, 2020)
Voloshchuk Yu.O., Voloshchuk V.R. FINANCIAL SUPPORT FOR INNOVATIVE DEVELOPMENT OF AGRO-INDUSTRIAL ENTERPRISESPurpose. The aim of the article is to substantiate the essence and mechanisms of financial support of innovative development of agro-industrial enterprises.Methodology of research. The dialectical method of scientific knowledge, systemic and logical approaches is used to accomplish certain tasks of research and achieve the set goal. In the process of research, the following general scientific methods are used: economics and statistics – to generalize the trends of innovation activity in Ukraine; tabular – for visual display of research results; abstract and logical – when forming conclusions.Findings. The tendencies and generalizations of the peculiarities for implementation of innovative processes are determined, the tools and sources of financing of innovative activity of agro-industrial enterprises are substantiated. The main directions of increasing the efficiency of innovation and investment activity of enterprises, which include the necessity of developing an optimal innovation strategy for development and making optimal managerial decisions, are systematized. The low level of competitiveness of the industries is revealed in comparison with the western countries and the reasons for it are substantiated.It is established that in order to increase the competitiveness of the branches of enterprises it is necessary to: protect investors’ rights and open access to lending to small and medium-sized businesses through special funds; create innovation and investment infrastructure; to introduce the mechanism of public testing of investment projects in agro-industrial enterprises; integrate investment law; to create a national system of insurance of investment risks in the implementation of long-term projects; integrate into the European investment area and adapt the legal framework to the MCAA; to establish the merger and acquisition procedure of enterprises legislatively in order to attract investments, as well as to ensure the proper level of regulation of these processes in order to avoid monopolization of foreign investors by leading branches of the national economy; to conduct an audit of the special modes of investment activity and to clarify the concept of their application; create a regulatory framework for relations with foreign investors; to legislatively establish the possibility of reorganization of corporate and unit funds.Originality. The tools for the implementation of innovative processes have further developed, the allocation of trends and sources of funding for innovative activities of agribusiness enterprises and the ability of the system to provide financial resources for innovative development for the further growth of the domestic economy, as well as the development and systematization of the legislative framework in the field of innovation and investment; regulation of mass innovations and determinants of attraction of foreign investments and determination of directions of activation of innovation and investment activity of agro-industrial enterprises.Practical value. The obtained results of the research can be used by enterprises and business to restore active investment processes in relation to the innovation activity of enterprises, as well as to ensure the effective protection of investors’ rights.Key words: investments; innovations; financing; scientific developments; innovation and investment activity; state.
Keywords: Key words; investments; innovations; financing; scientific developments; innovation and investment activity; state.